Insufficient dimensional stability of bitumen sheets as a source of flat roof defects - Plachý Jan (MATEC Web of Conferences, 2018)
One of the frequent sources of flat roof faults is failure of the top layer of a multilayer bitumen sheet system in cross-connections. One of the possible causes of this disorder is failure to observe technological discipline. The paper deals with how the full melting of the bitumen sheet influences its possible shrinkage during the roof exposure. Bitumen sheets with a polyester carrier which is not reinforced with fiberglass fibers are burdened with shrinkage effect. The preload is introduced into these belts during production. The aim is to show how is the effect on loosening the preload in the carrier layer with full-scale smelting during the realization of the waterproofing layer. The preload loosening experiment, expressed by the dimensional stability test according to ČSN EN 1107, was performed in a laboratory on two bitumen sheets.